"Tell Me Something Other Than to Use a Condom and Sex Is Scary": Memorable Messages Women and Gender Minorities Wish for and Recall about Sexual Health. Issue 4 (2nd October 2017) - Rubinsky, Valerie; Cooke-Jackson, Angela
ABSTRACT: This study explores how the memorable messages we receive and those we do not receive complicate the negotiation of sexual health and well-being among women and gender minorities. These powerful accounts reveal the tensions women and gender minorities experience managing what they were told about their sexual identity and sexual health by their parents and educators and those messages they wish they had received instead. Women and gender minorities recall memorable sexual health messages about abstinence, protection, and danger. Their recollections suggest that they want messages that center around positivity, pleasure, and dialogue, and that affirm diverse sexualities and genders. This work emphasizes that for parents and educators especially, what they do not say about sexual health may be just as impactful as what they do say.